Multicenter randomized controlled trial comparing the performance of 22 gauge versus 25 gauge EUS–FNA needles in solid masses. (July 2013) - Vilmann, Peter; SĂftoiu, Adrian; Hollerbach, Stephan; Skov, Birgit Guldhammer; Linnemann, Dorte; Popescu, Carmen Florina; Wellmann, Axel; Gorunescu, Florin; Clementsen, Paul; Freund, Ulrich; Flemming, Peer; Hassan, Hazem; et al.
Abstract Background and aims. Few randomized studies have assessed the clinical performance of 25-gauge (25G) needles compared with 22-gauge (22G) needles during endoscopic ultrasound-guided fine needle aspiration (EUS–FNA) biopsy of intra-abdominal lesions. We aimed to compare the diagnostic yield, as well as performance characteristics of 22G versus 25G EUS biopsy needles by determining their diagnostic capabilities, the number of needle passes as well as cellularity of aspirated tissue specimen. Methods. The study is a prospective, randomized, multicenter study. Patients were referred between January 2009 and January 2010 for diagnostic EUS including EUS-guided FNA of different lesions adjacent to the upper GI tract. All patients were randomized to EUS–FNA performed with either a 22G or 25G aspiration needle. Results. EUS–FNA was performed in 135 patients (62 patients with a 22G needle). Sensitivity and specificity of the 22G needle was 94.1% and 95.8%, respectively, and for the 25G needle 94.1% and 100%, respectively. Investigators reported better visualization and performance for the 22G needle compared to the 25G (p < 0.0001). The number of tissue slides obtained was higher for the 22G needle during the second and third needle passes (p < 0.05). We did not observe significant differences between the number and preservation status of obtained cells (p > 0.05). Conclusions. A significant difference was found between the two types of needles in terms of reduced visualization of the 25G needle and suboptimal performance rating. However, this did not impact on overall results since both needles were equally successful in terms of a high diagnostic yield and overall accuracy.